Cultivation of pomegranate - Blumenfeld A.; Shaya F.; Hillel R. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
This paper describes various aspects of pomegranate cultivation. Tradition, consumption and production target, recommended soil, fertilisation and fertirrigation, most common diseases and treatments, weed control, tree shape and orchard design, pruning, preharvest treatment of fruits, harvesting, packing, storage and needs for the future.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)